MicroRNA-21 Coordinates Human Multipotent Cardiovascular Progenitors Therapeutic Potential. (14th October 2014) - Richart, Adèle; Loyer, Xavier; Néri, Tui; Howangyin, Kiave; Guérin, Coralie L.; Ngkelo, Anta; Bakker, Wineke; Zlatanova, Ivana; Rouanet, Marie; Vilar, José; Lévy, Bernard; Rothenberg, Marc; et al.
Abstract : Published clinical trials in patients with ischemic diseases show limited benefit of adult stem cell-based therapy, likely due to their restricted plasticity and commitment toward vascular cell lineage. We aim to uncover the potent regenerative ability of MesP1/stage-specific embryonic antigen 1 (SSEA-1)-expressing cardiovascular progenitors enriched from human embryonic stem cells (hESCs). Injection of only 10 4 hESC-derived SSEA-1 + /MesP1 + cells, or their progeny obtained after treatment with VEGF-A or PDGF-BB, was effective enough to enhance postischemic revascularization in immunodeficient mice with critical limb ischemia (CLI). However, the rate of incorporation of hESC-derived SSEA-1 + /MesP1 + cells and their derivatives in ischemic tissues was modest. Alternatively, these cells possessed a unique miR-21 signature that inhibited phosphotase and tensin homolog (PTEN) thereby activating HIF-1α and the systemic release of VEGF-A. Targeting miR-21 limited cell survival and inhibited their proangiogenic capacities both in the Matrigel model and in mice with CLI. We next assessed the impact of mR-21 in adult angiogenesis-promoting cells. We observed an impaired postischemic angiogenesis in miR-21-deficient mice. Notably, miR-21 was highly expressed in circulating and infiltrated monocytes where it targeted PTEN/HIF-1α/VEGF-A signaling and cell survival. As a result, miR-21-deficient mice displayed an impaired number of infiltrated monocytes and a defective angiogenic phenotype that could be partially restored by retransplantation of bone marrow-derived cells from wild-type littermates. hESC-derived SSEA-1 + /MesP1 + cells progenitor cells are powerful key integrators of therapeutic angiogenesis in ischemic milieu and miR-21 is instrumental in this process as well as in the orchestration of the biological activity of adult angiogenesis-promoting cells. Stem Cells   2014;32:2908–2922